Fuzzy-arithmetic-based Lyapunov synthesis in the design of stable fuzzy controllers: A computing-with-words approach - Zhou, Changjiu (Zielona Góra: Uniwersytet Zielonogórski)
A novel approach to designing stable fuzzy controllers with perception-based information using fuzzy-arithmetic-based Lyapunov synthesis in the frame of computing with words (CW) is presented.
Keywords: fuzzy control; standard fuzzy arithmetic; constrained fuzzy arithmetic; Lyapunov synthesis; stability; computing with words; perception-based information; pole balancing mobile robot